2017
DOI: 10.1016/j.tibs.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

How Do J-Proteins Get Hsp70 to Do So Many Different Things?

Abstract: Hsp70 chaperone machineries play pivotal roles in a wide array of fundamental biological processes, through their facilitation of protein folding, disaggregation and remodeling. Hsp70’s obligate J-protein co-chaperones drive much of this remarkable multi-functionality, with most Hsp70s having multiple J-protein partners. Recent data suggest that J-protein-driven versatility is substantially due to precise localization within the cell and specificity of substrate protein binding. However, this relatively simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(199 citation statements)
references
References 79 publications
7
191
0
1
Order By: Relevance
“…Indeed, analysis of human DNAJC10 shows that it interacts with signaling molecules that are important in developmental processes, including EGF, TGF‐β, and Notch (Oka et al, ), which have an integral role in morphogenesis. It has been suggested that DNAJB11, DNAJC3, and DNAJB9 can also bind a variety of unfolded and/or misfolded proteins (Craig & Marszalek, ) but the extent of binding remains elusive. Knockdown of SEC63/ dnj‐29 showed a marked increase in variance, which might be due to the large number of interactions it might have as a translocon, a protein complex associated with translocation of polypeptide across membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analysis of human DNAJC10 shows that it interacts with signaling molecules that are important in developmental processes, including EGF, TGF‐β, and Notch (Oka et al, ), which have an integral role in morphogenesis. It has been suggested that DNAJB11, DNAJC3, and DNAJB9 can also bind a variety of unfolded and/or misfolded proteins (Craig & Marszalek, ) but the extent of binding remains elusive. Knockdown of SEC63/ dnj‐29 showed a marked increase in variance, which might be due to the large number of interactions it might have as a translocon, a protein complex associated with translocation of polypeptide across membranes.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Like many other J-proteins, Hsc20 interacts with substrate protein independently from its Hsp70 partner (Craig & Marszalek, 2017). Yet, the specificity of this interaction is quite unique, with Isu and Hsc20 forming a large binding interface.…”
Section: Hsc20–isu Interactionmentioning
confidence: 99%
“…Other domains of J-proteins are highly variable, in many cases displaying no sequence or structure similarities. Many J-proteins have a J-domain at their N-terminus followed by different types of domains that bind substrates, which allow them to interact with particular substrate proteins on their own, and as consequence to target substrate for Hsp70 binding (Craig & Marszalek, 2017). While J-proteins are obligatory, they only modestly stimulate Hsp70’s ATPase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp70 and Hsp90 chaperone systems play a role in different organelles of the eukaryotic cell and regulate a wide range of events including folding of de novo synthesized polypeptides, refolding, or degradation of misfolded proteins. Furthermore, they also show disaggregation activity, facilitate protein translocation through membranes and they are involved in remodeling of multimeric protein complexes . Hsp90 is also involved in regulation of receptor‐ligand binding or assembly of protein complexes, and has been implicated in regulatory pathways such as DNA repair or immune response .…”
Section: The Chaperone Networkmentioning
confidence: 99%